2009
DOI: 10.1099/vir.0.006569-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of murid herpesvirus-4 infection

Abstract: Luciferase-based imaging allows a global view of microbial pathogenesis. We applied this technique to gammaherpesvirus infection by inserting a luciferase expression cassette into the genome of murine herpesvirus-4 (MuHV-4). The recombinant virus strongly expressed luciferase in lytically infected cells without significant attenuation. We used it to compare different routes of virus inoculation. After intranasal infection of anaesthetized mice, luciferase was expressed in the nose and lungs for 7–10 days and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
149
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(151 citation statements)
references
References 57 publications
2
149
0
Order By: Relevance
“…7B), suggesting that other B-cell populations express mLANA at those time points. In addition, B cells, macrophages, and dendritic cells are latently infected at other sites, including the blood, lymph nodes, lung, and peritoneal cavity (16,17,39,54,65). Future experiments will be critical to determine whether mLANA is expressed in other major infected cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…7B), suggesting that other B-cell populations express mLANA at those time points. In addition, B cells, macrophages, and dendritic cells are latently infected at other sites, including the blood, lymph nodes, lung, and peritoneal cavity (16,17,39,54,65). Future experiments will be critical to determine whether mLANA is expressed in other major infected cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo imaging studies can be performed only on sufficiently smallanimal models to ensure effective transmission and detection of light (20), which renders rabbits difficult to use with this system. However, bioluminescent signals can effectively be detected from explanted organs of euthanized animals (28). In order to detect AlHV-1 infection ex vivo during WD-MCF, we used the recent BAC clone of the infectious and pathogenic C500 strain of AlHV-1 (13) and produced a recombinant strain expressing LUC as a reporter protein.…”
Section: Discussionmentioning
confidence: 99%
“…However SCLN infection is asynchronous, making early events hard to capture. This reflects the fact that mucosal penetration requires viral replication: a replicationdeficient mutant (ORF50 2 MHV-GFP; Milho et al, 2009) gave no EGFP + cells in SCLNs (data not shown). Therefore, we also tracked popliteal LN (PLN) infection after MuHV-4 inoculation into footpads (10 5 p.f.u.…”
mentioning
confidence: 97%